Zebraodes, new genus, with a new species from Vietnam (Lepidoptera: Tortricidae: Tortricinae: Archipini) - Heppner, John B.; Bae, Yang-Seop (Zootaxa, 2017)
A new genus of Tortricinae, Zebraodes Heppner & Bae, n. gen., is described for the new species Zebraodes lucidalis Heppner & Bae, n. sp., from Vietnam (Tortricidae: Tortricinae: Archipini). The new genus is anomalous among archipines, resembling some Ceracini, but with genital features more similar to those of Archipini, notably the strongly convex phallus in the male genitalia, together with the strong uncus; however, the absence of a signum in the female genitalia is unusual for the tribe.